Causal associations between circulating inflammatory cytokines and blinding eye diseases: a bidirectional Mendelian randomization analysis - Teng, Menghao; Wang, Jiachen; Su, Xiaochen; Tian, Ye; Ye, Xiaomin; Zhang, Yingang (Frontiers in Aging Neuroscience, 2024)
Background Previous studies have explored the associations between circulating inflammatory cytokines and blinding eye diseases, including glaucoma, cataract and macular degeneration. However, the causality of these associations remains controversial. This study employs a bidirectional Mendelian randomization (MR) study to investigate the causal relationships between 41 circulating inflammatory cytokines and these blinding eye diseases. Methods Summary data for glaucoma, cataract, macular degeneration and 41 circulating inflammatory cytokines were publicly available. The inverse variance weighted (IVW) method was employed as the main analysis method. Additionally, various sensitivity tests, including MR–Egger regression, weighted median, weight mode, Cochran’s Q test, MR pleiotropy Residual Sum and Outlier test, and leave-one-out test, were conducted to evaluate sensitivity and stability of results. Results The IVW analysis identified six circulating inflammatory cytokines causally associated with the risk of blinding eye diseases: Monokine induced by interferon-gamma (MIG) for glaucoma, interleukin-1 receptor antagonist (IL-1ra), IL-6, IL-10, and platelet derived growth factor BB (PDGFbb) for cataract, and MIG and hepatocyte growth factor (HGF) for macular degeneration. However, it is noteworthy that none of these associations remained significant after Bonferroni correction (p < 0.0004). Reverse MR analyses indicated that cataract may lead to a decrease in vascular endothelial growth factor (VEGF) levels (OR: 3.326 × 10−04, 95% CI: 5.198 × 10−07 − 2.129 × 10−01, p = 0.0151). Conclusion This study highlights the potential roles of specific inflammatory cytokines in the development of glaucoma, cataract and macular degeneration. Moreover, it suggests that VEGF is likely to be involved in cataract development downstream. These findings offer insights for early prevention and novel therapeutic strategies for these blinding eye diseases.